Evaluation of cutting force and surface roughness in the dry turning of Al-Mg2Si in-situ metal matrix composite inoculated with bismuth using DOE approach - Razavykia, Abbas (Elsevier, 2015)
Al-Mg2Si particulate metal matrix composites (PMMC) has recently received wider attention because of its improved properties, however there is a lack of knowledge about machinability characteristics of these composites especially with bismuth addition. The purpose of this study is to evaluate the machining parameters and modifier element effects on cutting force (Fc) and surface roughness (Ra) when dry turning Al-Mg2Si with a coated carbide tool (K10U). The experimental trials are designed using the multi-level factorial design (DOE) and their results are analyzed using Analysis of Variance (ANOVA). Statistical models are developed to represent the relationship among machining parameters as independent variables, surface roughness and cutting force as response variables. For each experiment, a new cutting insert is used to encourage accurate reporting of the cutting force and surface roughness. The statistical observation revealed that the main effect of cutting speed, feed rate and modifier element influenced the cutting force and surface roughness. Moreover, there are no interaction effects of variables. Built-up-edge (BUE) formation was observed at every combinations of cutting speed and feed rate which affected the surface quality negatively. The proximity of predicted results and experimental results provide evidence that the DOE method has successfully derived the predictive models. The addition of Bi as modifier reagent results in lower cutting force and better surface roughness due to the formation of Bi compound and modifies the morphology of Mg2Si reinforcement particle. Our findings showed that the Bi is a promising element to improve the machinability of Al-Mg2Si composite.